There are rivers in the sky - Shafak, Elif. 1971- (London: Penguin, 2024)
"Sweeping across centuries, and stretching from Mesopotamia to London, this is an enchanting new novel by Booker Prize finalist Elif Shafak that conjures a trio of characters living in the shadow of one of the greatest epic poems (The Epid of Gilgamesh) of all time"--
English.
Keywords: Novels